Body weight support impacts lateral stability during treadmill walking. Issue 13 (6th September 2016) - Dragunas, Andrew C.; Gordon, Keith E.
Abstract: Body weight support (BWS) systems are a common tool used in gait rehabilitation. BWS systems may alter the requirements for an individual to actively stabilize by 1) providing lateral restoring forces that reduce the requirements for the nervous system to actively stabilize and 2) decreasing the stabilizing gravitational moment in the frontal plane, which could increase the requirements to actively stabilize . The goal of the current study was to quantify the interaction between BWS and lateral stability. We hypothesized that when able-bodied people walk with BWS: 1) the lateral restoring forces provided by BWS would reduce the requirements to stabilize in the frontal plane when comparing dynamically similar gaits, and 2) increasing BWS would decrease the stabilizing gravitational moment in the frontal plane and increase the requirements to stabilize when speed is constrained. Our findings partly support these hypotheses, but indicate a complex interaction between BWS and lateral stability. With BWS, subjects significantly decreased step width variability and significantly increased step width ( p <0.05) for both the dynamically similar and Speed-Matched conditions. The decrease in step width variability may be attributable to a combination of lateral restoring forces decreasing the mechanical requirements to stabilize and an enhanced sense of position that could have improved locomotor control. Increases in step width when walking with high levels of BWS could have been due to decreases in the gravitational moment about the stance limb, which may challenge the control of stability in multiple planes.